Symbolika laski marszałkowskiej w świetle zachowanej ikonografii i literatury - Mielnik, Paulina Anna (Motywy fauny i flory w literaturze i kulturze, 2018)
This article is an attempt to answer a question how does the Marshall’s cane, shown from different scientific prospects, includes allegorical meaning. As the attribute of Marshall’s office it was an important communicative item. Alongside with a written word, verbal system as well as a picture, sign and symbol were means of transmission for illiterate community. The cane is the emblem of power and refinement, equipped in a rich symbolism, empowers and constructs the dignity of Marshall’s office. Fauna and flora motives visible in its complex system of symbolism emphasizes additionally its value.